The Culture Reproduction In the Charles Dickensâ€™ Novel â€œGreat Expectationsâ€ (Pierre-Felix Bourdieu Theory) - Nur, Askar (Talenta Publisher, 2021)
This research discusses cultural reproduction in Charles Dickens' novel Great Expectations and aims to discover the process of cultural reproduction in the novel. The researcher used the culture reproduction (habitus and field concept) theory of Pierre-Felix Bourdieu. This research focuses on culture reproduction that occurred in Great Expectations. The data were analyzed using a descriptive qualitative method to identify, describe and analyze the data found in the novel. The researcher used a coding sheet as the instrument to find out the valid data. This research is conducted to answer the problems that concerning how cultural reproduction occurred in the novel. According to Bourdieu, the findings show that some phenomena supported the process of cultural reproduction, as following the phenomena of cultural reproduction in the old and new culture based on habitus and field concept and its dialectical relation. The researcher concludes that the dialectical relation between old and new habitus, the old and new arena (field) or between unwillingness to return to old life and unwillingness to live in new life makes Pip get into a new phase of life by bringing his old culture and current culture.